MR Imaging–Based Correction for Partial Volume Effect Improves Detectability of Intractable Epileptogenic Foci on Iodine 123 Iomazenil Brain SPECT Images: An Extended Study with a Larger Sample Size - Kato, H. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: It has been suggested, on the basis of a previous pilot study conducted in a small number of patients, that MR imaging–based PVE correction in I-123 iomazenil brain SPECT improves the detectability of cortical epileptogenic foci. In the present study, we performed an investigation by using a larger sample size to establish the effectiveness of the PVE correction and to conduct a detailed evaluation based on the histologic classification of lesions. MATERIALS AND METHODS: Seventy-five patients (male/female, 37/38; age, 28 ± 12 years) with intractable epilepsy who had undergone surgical treatment were enrolled in this study. I-123 iomazenil SPECT and MR imaging examinations were performed before the operation in all patients. I-123 iomazenil SPECT images with and without MR imaging–based PVE correction were assessed visually and by semiquantitative analysis based on the AI(%) of the SPECT count in the resected lesions. RESULTS: The sensitivity, specificity, and accuracy of foci detection by visual assessment were significantly higher after PVE correction compared with the values obtained before the correction. The results of the semiquantitative analysis revealed that the asymmetry of the SPECT counts was significantly increased after the PVE correction in the surgically resected lesions in cases of mesial temporal sclerosis, tumor, and malformations of cortical development. CONCLUSIONS: The effectiveness of MR imaging–based PVE correction in I-123 iomazenil brain SPECT in improving the detection of cortical epileptogenic foci with abnormal histologic findings was established by our investigation conducted on a large sample size.